KNOWLEDGE MANAGEMENT AND ORGANIZATIONAL COMPETITIVENESS - Dželetović, Milenko; Mašić, Branislav M; Nikolić, Davor M.; Nešić, Sandra B. (Poslovna ekonomija, 2017)
More that 20 years ago, Drucker promoted knowledge as the “basic economic resource“; he furthermore argued that it (knowledge) has become the only resource for competitive advantage. We could say that organization’s capability to initiate and implement actions and processes of exploiting existing knowledge and creating new “knowledges” is among key-factors in creating competitive advantage. Aiming to unique knowledge creation would certainly differentiate a company from others, but recognizing both tacit and explicit knowledge, and establishing proper infrastructure are as important aspects. Concept of Knowledge Management, recognized as one of the most important management tools, is widely used, although new technologies and changing business environment require continual adjustments. Neverthless, we consider knowledge to be valuable and even critical success factor of companies.